1988
DOI: 10.1128/iai.56.1.28-33.1988
|View full text |Cite
|
Sign up to set email alerts
|

Identification and properties of Trichomonas vaginalis proteins involved in cytadherence

Abstract: Trichomonas vaginalis NYH286 surface proteins which are candidates for mediating parasite cytadherence (adhesins) were identified. At least four trichomonad protein ligands ranging in relative molecular mass from 65 to less than or equal to 21 kilodaltons were found to selectively bind to chemically stabilized HeLa cells. The proteins were present on the surfaces of 10 different isolates of T. vaginalis examined; however, the nonpathogenic trichomonad T. tenax did not possess similar HeLa cell-binding proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
84
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 20 publications
12
84
0
Order By: Relevance
“…Lactoferrin binding was measured as described in the Experimental procedures. Protein synthesis of cycloheximide-treated organisms was inhibited as has been described (Aiderete and Garza, 1988). The inset demonstrates the return to baseline levels of lactoferrin binding after addition of iron {O) but not trace metal solution (•) (Linstead, 1981) of parasites grown under stringent iron-limitation.…”
Section: Specific Iron Regulation Of Expression Ofl Vaginalis Iactofmentioning
confidence: 86%
“…Lactoferrin binding was measured as described in the Experimental procedures. Protein synthesis of cycloheximide-treated organisms was inhibited as has been described (Aiderete and Garza, 1988). The inset demonstrates the return to baseline levels of lactoferrin binding after addition of iron {O) but not trace metal solution (•) (Linstead, 1981) of parasites grown under stringent iron-limitation.…”
Section: Specific Iron Regulation Of Expression Ofl Vaginalis Iactofmentioning
confidence: 86%
“…Despite that four-trichomonad surface adhesins: AP65, AP51, AP33 and AP23, have been identified and characterized previously (Alderete and Garza, 1988;Arroyo et al, 1992), no putative receptors on the human urogenital cells have been identified for any of them yet. Nevertheless, in this work, we showed the identification of a putative receptor to the AP120 adhesin in HeLa cells, a 130 kDa surface protein.…”
Section: Discussionmentioning
confidence: 99%
“…The inability of APs to enter the secretory pathway that was demonstrated in this study is in direct contradiction to previous investigations. Polyclonal rabbit antisera against AP65 and AP51 ( Alderete and Garza 1988;Arroyo et al 1992) have been used as Golgi markers for the investigation of Golgi structure and division within the T. vaginalis cell cycle . AP65 antiserum strongly labeled Golgi ribbons and a few vesicles in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…The last group of proteins includes the enzymes pyruvate ferredoxin oxidoreductase (PFO), malic enzyme, and the aand b-subunits of succinyl-CoA synthetase (SCS), which mediate key steps of energy metabolism in hydrogenosomes (Brugerolle et al 2000;Drmota et al 1996;Hrd y and M€ uller 1995;Lahti et al 1992Lahti et al , 1994. Curiously, the same proteins have been reported to function as the surface adhesins AP120 (PFO), AP65 (malic enzyme), AP33 (a-SCS), and AP51 (b-SCS) (Alderete and Garza 1988;Alderete et al 1995a,b;Arroyo et al 1992;Moreno-Brito et al 2004). As adhesin proteins (APs), they are proposed to mediate the cytoadherence of T. vaginalis to vaginal epithelial cells (VECs; Alderete and Garza 1988;Alderete et al , 1995a.…”
mentioning
confidence: 99%
See 1 more Smart Citation